Dataset koleksi anggrek: Eksplorasi flora Samosir, Sumatera Utara - Suminarsih, Eka Meifrina; Puspitaningtyas, Dwi Murti (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2024)
Sumatra Island, with its tropical climate, provides an ideal habitat for orchid diversity. However, the rich diversity and potential of these orchids are increasingly threatened by high deforestation rates across Indonesia, leading to risks of reduction and even extinction. To address this, conservation activities are underway at the Samosir Botanic Garden. This study aimed to inventory the orchid diversity on Samosir Island. Collected orchids are being conserved as a living collection both ex situ at the Bogor Botanic Garden and in situ at the Samosir Botanic Garden. An exploratory method was used, resulting in a collection of 80 orchid specimens, representing 35 genera, 80 species, and 313 individual samples. These orchids were found at altitudes ranging from 989 to 1,799 meters above sea level and included 60 epiphytic species, 1 lithophytic species, and 19 terrestrial species. A total of 23 orchid species were identified during the exploration, and data on these species are stored in the National Scientific Repository (RIN). This repository provides a valuable resource for further research on the orchid species richness in Samosir Regency.